A case study in cross-talk: the histone lysine methyltransferases G9a and GLP - Collins, Robert (Oxford University Press, 2010)
The histone code hypothesis predicts that the post-translational modification of histones can bring about distinct chromatin states, and it therefore serves a key regulatory role in chromatin biology. The impact of one mark on another has been termed cross-talk. Some marks are mutually exclusive, while others act in concert. As multiple marks contributing to one outcome are generally brought about by complexes containing multiple catalytic and binding domains, it appears regulation of chromatin involves a web of writers and readers of histone modifications, chromatin remodeling activities and DNA methylation. Here, we focus on the protein lysine methyltransferases G9a and GLP as examples of this extended cross-talk. G9a and GLP can catalyze the formation of and bind to the same methyl mark via distinct domains. We consider the impact of other histone modifications on G9a/GLP activity and the coordination of activities within G9a/GLP containing complexes. We evaluate the potential impact of product binding on product specificity and on maintenance and propagation of the methyl mark. Lastly, we examine the recruitment of other silencing factors by G9a/GLP. Regulated assembly of specific complexes around key marks may reinforce or alter the biological outcome associated with given histone modifications.